Jorge Basadre or the will to persist - Flores Galindo, Alberto (1980)
Just a few months ago, Basadre published his latest book dedicated to the study of the electoral mechanisms used by the oligarchic state. The original project implied a profound renovation of our political history with the use of extensive quantitative material that would be processed by computers, but ironically, the historian of the republic did not find the necessary financing to carry out his project and the book in question ended up in what would amount to a preliminary report; apparently the investigation was inconclusive.